Hands-on security in DevOps : ensure continuous security, deployment, and delivery with DevSecOps - Hsu, Tony (Packt Publishing, 2018)
Hands-On Security in DevOps explores how the techniques of DevOps and Security should be applied together to make cloud services safer. By the end of this book, readers will be ready to build security controls at all layers, monitor and respond to attacks on cloud services, and add security organization-wide through risk management and training.